LAIV Mutations Selectively Alter Influenza Viral RNA Polymerase Function, Favoring Transcription over Genome Synthesis - Leach, Justin R.; Oo, Adrian; Nogales, Aitor; Bosch, Sebastian I.; Martínez-Sobrido, Luis; Feng, Changyong; Kim, Baek; Dewhurst, Stephen (Viruses, 2025)
Influenza viruses cause mild to severe lower respiratory infections, sometimes resulting in hospitalization and death. Vaccination remains the primary prophylactic strategy. Live attenuated influenza vaccines (LAIVs) efficiently induce antiviral immune responses and contain temperature-sensitive and cold-adapted mutations that render them safe. These mutations are principally located in the PB1 and PB2 subunits of the viral RNA polymerase, but the mechanism by which they attenuate the virus is unclear. We introduced the PB1 and PB2 mutations from two LAIV backbones, A/Ann Arbor/6/1960 H2N2 (AA) and A/Leningrad/134/17/1957 H2N2 (Len), into the model influenza strain A/Puerto Rico/8/1934 H1N1 (PR8). In contrast to the wild-type (WT) PR8 polymerase, the two “PR8-LAIV” polymerase complexes demonstrated maximal activity at cold temperatures (30–32 °C) and greatly reduced activity at elevated temperatures (>37 °C). To further understand the impact of the LAIV mutations, we infected MDCK cells with WT and mutated PR8 viruses that contain the Len and AA LAIV mutations in PB1 and PB2. The PR8-LAIV mutant viruses exhibited a selective, temperature-dependent defect in the replicase activity of the viral RNA polymerase relative to WT PR8, while also demonstrating a temperature-dependent enhancement in the transcriptional activity of the enzyme. In addition, the PR8-LAIV mutant viruses produced similar levels of viral proteins to WT PR8 at 37 °C, but greatly (2–3 log10) reduced levels of infectious viral progeny. Collectively, these data show that LAIV mutations selectively alter influenza viral RNA polymerase function, favoring transcription over genome synthesis at 37 °C, thereby preserving viral antigen production while also contributing to viral attenuation.